Tra silicio e carbonio: le macchine saranno sempre stupide? (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The convergence of biochemistry, molecular biology, physiology, linguistics, philosophy, cognitive psychology, behavioral genetics, neurosciences, nanosciences in the most advanced developments of mechanics and electronics make the dividing line between organic and inorganic and between material and immaterial less and less clear. A particular form of intelligence arises from machines and develops by machines, going beyond machines. There is no telling how far.
Keywords: Artificial intelligence; lab-grown brains; extreme summarization; hallucinating algorithms; subject/object